Pelatihan Perencanaan dan Strategi Pembelajaran pada Program Teachers Transformation Center Majelis Pendidikan Kristen di Indonesia - Lastiar Roselyna Sitompul (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
As a christian educator, a teacher must have a whole competence in doing their calling. Thus, one of the competencies that a Christian teacher should have is a pedagogical competence, such as teaching plan and teaching strategies. This competence is very important for the role of a Christian teacher as a structuring, especially planning of the class community activities. This training program is held to enable teachers canditate in designing teaching plan and teaching strategie. Moreover, it is organized by the christian education council and aimed to equip the christian teachers candidate to be qualified teachers, having transformational abilities as well as Biblical Christian Worldview. This training is a very strategic opportunity to train Christian teachers candidate who will be placed in various regions in Indonesia. This program needs to be supported by participation in community service activities as teachers trainer. This training program includes teaching plan, determining learning objectives, teaching strategies, models and media of teaching. The result of this training were that participants are able to arrange a systematic lesson planning, directed and organized lesson planing, learning strategies with various approaches and methods that answer the needs of students in learning and compile learning planning steps, including determine learning objectives, selecting learning experiences, determine learning activities. Keywords: Learning strategies, Teaching planning